(untitled) (Academicia Globe: Inderscience Research, 2022)
Currently, the natural environment of the Akhangaran river valley is experiencing a high technogenic impact. At the same time, fresh groundwaters of the Quaternary hydrogeological complex, which are the main source of household and drinking water supply in the region, are experiencing the greatest negative impact. There is a change in hydrogeological conditions, transformation of groundwater and the formation of technogenic ecological and hydrogeological systems under the influence of technogenesis.